Pengaruh proses swelling dengan supercritical gas CO2 terhadap penurunan energi ikatan senyawa hidrokarbon vacuum residue - Deby Ansyory; Aditya Retno Utami; Sri Haryati; Muhammad Djoni Bustan (Jurnal Rekayasa Proses, 2019)
The present study aims to develop technology to utilize a vacuum residue by reducing its density, viscosity and energy bonding, using a batch reactor equipped with CO2 injection gas in the form of a swelling process. The study was conducted by applying temperature varied between 60 and 100 °C and CO2 flux pressure varied between 1 and 5 MPa, respectively. The study of applying temperature and CO2 flux pressure are used to decrease the bond energy of hydrocarbon compounds in the form of solid vacuum residue. Furthermore, a series of reaction time was carried out started in the range of 10-30 minutes to obtain the optimum reaction time. The result showed that at temperature of 100°C, pressure of 5 MPa and variation of time, the density, viscosity, and decrease in energy bonding (ΔG) were in the range of 0.919-0.902 g/cm3, 495-166 cSt, and 8.627–6.436 J.s, respectively.